Vaccinia virus morphogenesis is blocked by a temperature-sensitive mutation in the I7 gene that encodes a virion component. - Kane, E M (1993)
The ts16 mutation of vaccinia virus WR (R. C. Condit, A. Motyczka, and G. Spizz, Virology 128:429-443, 1983) has been mapped by marker rescue to the I7L open reading frame located within the genomic HindIII I DNA fragment. The I7 gene encodes a 423-amino-acid polypeptide. Thermolabile growth was attributed to an amino acid substitution, Pro-344-->Leu, in the predicted I7 protein. A normal temporal pattern of viral protein synthesis was elicited in cells infected with ts16 at the nonpermissive temperature (40 degrees C). Electron microscopy revealed a defect in virion assembly at 40 degrees C. Morphogenesis was arrested at a stage subsequent to formation of spherical immature particles. Western immunoblot analysis with antiserum directed against the I7 polypeptide demonstrated an immunoreactive 47-kDa polypeptide accumulating during the late phase of synchronous vaccinia virus infection. Immunoblotting of extracts of wild-type virions showed that the I7 protein is encapsidated within the virus core. The I7 polypeptide displays amino acid sequence similarity to the type II DNA topoisomerase of Saccharomyces cerevisiae.